RAMIPRIL EFFICACY IN PATIENTS WITH ARTERIAL HYPERTENSION AND ISCHEMIC HEART DISEASE - A. I. Chesnikova; I. N. Koshenskaja; V. P. Terentyev; N. N. Mozhaeva; I. V. Bedareva; L. A. Lavrik; T. V. Zhertovsky (Рациональная фармакотерапия в кардиологии)
Aim. To study ramipril effect on parameters of ambulatory blood pressure (BP) monitoring, cardio-vascular remodeling parameters in patients with arterial hypertension (HT) and ischemic heart disease (IHD).Material and methods. 40 patients with HT (stage 1-2) combined with IHD (functional class 1-2) were included in the study. All patients were randomized in 2 groups. Patients of the 1st group received basic therapy with aspirin, statin and ß-blocker. Patients of the 2nd group received the same therapy as well as ACE inhibitor ramipril (Hartil, EGIS). Changes in clinical status, daily BP profile, cardio-vascular remodeling parameters were evaluated.Results. After 12 week treatment clinical improvement was revealed in the both groups of the patients. Ramipril contributed additional pulse BP and BP loading reduction, regression of left ventricular hypertrophy, improvement of systolic and diastolic left ventricle function, increase in brachial artery diameter.Conclusion. Ramipril inclusion in the basic therapy of patients with HT and IHD increases in efficacy of antihypertensive treatment and improves structural and functional conditions of heart and vessels.